Architecture recovery of web applications - Hassan, Ahmed E.; Holt, Richard C. (Proceedings - International Conference on Software Engineering, 2002)
Web applications are the legacy software of the future. Developed under tight schedules, with high employee turn over, and in a rapidly evolving environment, these systems are often poorly structured and poorly documented. Maintaining such systems is problematic.This paper presents an approach to recover the architecture of such systems, in order to make maintenance more manageable. Our lightweight approach is flexible and retargetable to the various technologies that are used in developing web applications. The approach extracts the structure of dynamic web applications and shows the interaction between their various components such as databases, distributed objects, and web pages. The recovery process uses a set of specialized extractors to analyze the source code and binaries of web applications. The extracted data is manipulated to reduce the complexity of the architectural diagrams. Developers can use the extracted architecture to gain a better understanding of web applications and to assist in their maintenance.